IMPLEMENTASI PROGRAM PAGI CERIA DALAM MEMBENTUK KARAKTER MURID KELAS 1B SEKOLAH DASAR - Putri Akbarwati; Nur Hidayatul Hasanah; Nur Aida Fitriyana; Arfilia Wijayanti; Maryati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of the Pagi Ceria Program in shaping the disciplined and harmonious character of first-grade students at SDN Pandeanlamper 03, as well as its impact on the transformation of teachers' pedagogical competence. This study uses a descriptive qualitative method with data collected through participatory observation, in-depth interviews, and documentation. The subjects of the study were first-grade B students, teachers, and the school principal. The results of the study indicate that the program effectively shaped student character through four main activities: singing the Rukun Sama Teman song achieved the highest success rate at 95% (excellent category) as it effectively reduced social anxiety through hand-holding interactions, followed by the Flag Respect ritual at 90% (excellent category) in building nationalism, Morning Gymnastics at 85% (good category) in stimulating motor fitness, and the Seven Habits Gymnastics at 70% (fair category) due to students' limited attention span in following movement instructions. Furthermore, the short attention span and volatile moods of early childhood students triggered a significant transformation in teachers' pedagogical skills. Teachers shifted from rigid one-way instructions to utilizing communication-persuasive soft methods and positive reinforcement through the Apresiasi Jempol strategy, creating a supportive and child-friendly learning environment.